Predictors, Classification, and Management of Umbilical Complications in DIEP Flap Breast Reconstruction. Issue 1 (July 2017) - Cho, Min-Jeong; Teotia, Sumeet S.; Haddock, Nicholas T.
Abstract : Background: In recent years, the deep inferior epigastric perforator (DIEP) flap has become the workhorse flap for autologous breast reconstruction. Despite increased reports on DIEP flaps, umbilical complications have not been previously studied. The aesthetics of the umbilicus dictates the beauty of the abdomen, and it is critical for plastic surgeons to minimize the scarring of the umbilicus. In this study, we retrospectively reviewed patients who underwent DIEP flaps to determine the predictors of umbilical complications, and created a classification system of these wounds. Methods: Retrospective review of 323 patients who underwent DIEP flap surgery from 2009 to 2016 was performed. Umbilical stalk heights, widths of fascial diastasis, and abdominal wall thicknesses were measured from computed tomographic scans. Data regarding demographic and patient characteristics were collected. Results: Of the 323 patients, there were 58 patients that had umbilical complications (18 percent). These patients had statistically higher body mass indexes, heavier flaps, and thicker abdominal walls ( p < 0.05). Also, they had statistically higher umbilical stalk heights (29.3 mm versus 18.7 mm), and analysis showed that the likelihood ratio of having umbilical complications was 2.05 at 20.1 mm, 3.05 at 25.4 mm, and 6.43 at 30 mm. Logistic regression analysis revealed that umbilical stalk height, fascial diastasis, age, procedure time, and flap weight were significant predictors ( p < 0.05). Conclusions: Umbilical complications in patients undergoing DIEP flap surgery for breast reconstruction have not been previously studied. Our study shows that the umbilical stalk height plays a significant role, and umbilical wounds can be classified into five types: no wound, minor wound, wound dehiscence, partial necrosis, and total necrosis. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.